The Abazans in turkish archival sources of the 19th century - Murat I. Mukov (Кавказология)
The article seeks to demonstrate Abazins’ status and role in Ottoman Empire policies in the Caucasus, particularly the terrible events of their relocation to the Ottoman Empire during the “Caucasian War” of 1763-1864. Documents from the state archives of Turkey, open to a wide range of researchers, demonstrate, in particular, the participation of the Abazins in military operations on the side of the Ottoman Empire, and also reveal the Turkish understanding of the role and place of Islam in the life of the North Caucasian peoples. Of particular importance are archival documents that record the names of villages founded by Abazin immigrants. The study of the territory of settlement of the Abazins in the Ottoman Empire and the territory of their residence in modern Turkey allows us to study both the history of specific Abazin settlements and the history of Abazin migration in new conditions. The analyzed sources concerning the state policy of the Ottoman Empire in the field of secular and spiritual education allow us to conclude that the emergence of a significant number of Turkish Abazins who received education and professional training is directly related to the fact that one hundred and fifty years ago, mosques and schools were built in the villages of Abazin immigrants, and the organizational and financial functioning of these institutions was ensured.